THE ROLE OF ORAL CAVITY HYGIENE AND ITS IMPACT ON PROSTHETIC STABILITY IN PATIENTS USING REMOVABLE AND FIXED PROSTHESES - Rajabova Mohira Ergashovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Maintaining optimal oral hygiene is crucial for patients using dental prostheses, as it directly influences prosthetic stability, longevity, and overall oral health. Poor hygiene can lead to complications such as inflammation, secondary caries, and prosthetic failure. A cross-sectional study was conducted involving 150 patients (75 with removable and 75 with fixed prostheses). Oral hygiene status was assessed using the Plaque Index (PI) and Gingival Index (GI). Prosthetic stability was evaluated clinically through mobility testing and patient-reported satisfaction surveys. Statistical analysis was performed to determine correlations between hygiene levels and prosthetic stability.